WEB ASSISTED LANGUAGE LEARNING (WALL) AND LEARNING MANAGEMENT SYSTEMS (LMS) IN VIRTUAL CENTRES FOR FOREIGN LANGUAGES - Ruiperez, German (International Journal of English Studies, 2002)
The Web has had different uses in the teaching of modern languages: (a) as a source of resources: In a very short time, the Web has become the largest source of resources for the learning of any foreign language; (b) as a window of multimedia applications (in this way CD-ROM is replaced by the Web as the main means of storage of multimedia applications.); and (c) as an e-learning platform.For an institution to create a Virtual Centre for Foreign Language Learning, certain software must be installed in a computer connected to the Internet. This software is called a Learnig Management Systein (LMS). Apart from the basic functions of the majority of the LMS, we should mention the advanced functions of the LMS: voice chats, digital television channel. mobile telephone services. WAP complementary services and access to the LMS through electronic pocket diaries (PDA). There are many comparative studies of LMS, carried out by consultants, specialist magazines, etc. Despite the proliferation of comparative studies of LMS. they have hardly considered the specific features of CALL software, in which the functions that pronote sound interaction should be more advanced. On the other hand, the subject of standards Iias become relevant. It is logical that the user who introduces contents into a given LMS would want the guarantee of being able to use those contents within another LMS.